Kajian Sosiologi Pengarang Terhadap Puisi al- Athlal Karya Ibrahim Najiy - Kuswoyo, Intan Handita (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2023)
Literature represents humans in various actions to achieve desired desires. Arabic literature and culture are very important and cannot be separated. In its development, Arabic literature could not be separated from Western influences, so that apart from poetry, new types of literary works, prose and drama, began to develop. The entry of Westerners brought influence and progress to Arabic literature until it reached the period of revival or 'ashr an-nahdlah. This revival phase is divided into two, namely the traditional phase and the renewal phase which gave rise to the neoclassical school. And next, the renewal movement was born as a result of the influence of Western romanticism, one of which was Madrasah Apollo and Ibrahim Najiy as one of its members. This article aims to discover the sociology of author Ibrahim Najiy regarding his phenomenal work al-Athlal. The research method used in this research is an expressive approach to analyzing literary works and their relationship to the author. A historical approach will also be used to conduct research on the authenticity of al-Athlal's poetry. So that we can get the sociology of the author of this phenomenal poetry of al-Athlal.